Distribution of jurisdiction among administrative judiciary bodies according to the latest developments in the constitutional amendment of 2020 - Seddiki, Nabila (The International tax journal, 2025)
The administrative judiciary system testified with the issuance of the 2020 Constitution, a significant structural reform that imposed the existence of new judicial bodies, represented by the creation of administrative appeal courts, thus completing the administrative judiciary pyramid similar to the ordinary judiciary. This change at the structural level required a change at the level of jurisdiction rules and at the level of procedural rules in general. Accordingly, in this study, we will focus on the rules for distributing the type and regional jurisdiction among administrative judiciary bodies after the creation of the new bodies, and the extent to which this is reflected in the evaluative jurisdiction of the Council of State, in light of what was approved by Organic Law 22-10 related to the judicial organization, Law 22-13 amending and supplementing the Code of Civil and Administrative Procedures, and Organic Law 22-11 amending and supplementing the law related to the organization, functioning and jurisdiction of the Council of State.